If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 + -6x = -11 Reorder the terms: 2 + 5x + -6x = -11 Combine like terms: 5x + -6x = -1x 2 + -1x = -11 Solving 2 + -1x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = -11 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -11 + -2 -1x = -11 + -2 Combine like terms: -11 + -2 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 702/u=27 | | 18.94+15.8g=-3(-18.8g+11.28) | | a-42=-4a-7 | | 5(8+2x)=-30 | | -2x+4-2x=-12 | | 18.94-15.8g=-3(-18.8g+11.28) | | 5+5d=80 | | 7r+3-3r=15 | | X-5+9x=40 | | z^2+(12+6i)z+(11+24i)=0 | | 80=18+2p | | 2x+9+4x=-57 | | 4.3f-14.65-19.08=-3.13+12.8f | | -x+2x+5+2x=-25 | | 6n^2-18n-18=-6 | | 9v-17=73 | | 2[5x+8]=6x+20 | | 9.7u-18.15-2.5u=11.8u+7.15 | | 43=8m+3 | | -2x+8-6x=-32 | | 15.5k-19.69+7.75=0.03+16.4k | | 7x-8-3x=20 | | 3x+10+4x=38 | | 25x+8=6x+20 | | -7+6x-5x=-19 | | 36=6x+5x+3 | | 3x-20=x-15 | | -16s+13+s=-5-14s | | -9p-6p-10=-14p+10 | | 5x-x-2x+2=12 | | 2x^2-45x-8=0 | | -15-10m=-20m-10m+5 |